Glass solid electrolyte and lithium ion battery

By adjusting the molar ratio of lithium, phosphorus, sulfur and halogen, and combining powder X-ray diffraction and mechanical blanking technology, glass solid electrolyte with high filling rate and high ionic conductivity was prepared, and the existing Li3PS4 glass solid electrolyte ions were solved. The problem of low conductivity is suitable for high-performance lithium-ion batteries.

CN119452431APending Publication Date: 2025-02-14IDEMITSU KOSAN CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380050892.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Among the existing lithium-ion batteries, the Li3PS4 glass solid electrolyte has a low ion conductivity and the filling rate is not enough to meet the needs of high-performance batteries.

Method used

By adjusting the molar ratio of lithium, phosphorus, sulfur and halogen, a glass solid electrolyte containing bromine or iodine is prepared to ensure that the molar ratio of lithium to phosphorus is between 2.0 and 5.3, and the molar ratio of sulfur to phosphorus is 2.0. Between ~4.5, the molar ratio of halogen to phosphorus is between 0.7 and 2.3, and its filling rate and ionic conductivity are improved through powder X-ray diffraction and mechanical blanking technology.

Benefits of technology

The glass solid electrolyte with high filling rate and high ionic conductivity is suitable for high-performance lithium-ion batteries and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119452431A_ABST
    Figure CN119452431A_ABST
Patent Text Reader

Abstract

The present invention relates to a glass solid electrolyte containing lithium, phosphorus, sulfur, and a halogen as constituent elements, the halogen containing at least bromine, the molar ratio (L i / P) of lithium (L i) to phosphorus (P) being 2.0-5.3, the molar ratio (S / P) of sulfur (S) to phosphorus (P) being 2.0-4.5, and the molar ratio (X / P) of halogen (X) to phosphorus (P) being 0.7-2.3, and showing a peak derived from lithium bromide in powder X-ray diffraction using CuK alpha rays.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a glass solid electrolyte and a lithium ion battery. Background Art

[0002] In order to improve the performance of lithium-ion batteries, it is important to increase the filling rate (compactness) of solid electrolyte powder. In order to increase the filling rate, it is effective to mechanically make the solid electrolyte soft (easy to compress and deform).

[0003] Among lithium ion conductive sulfide solid electrolytes, glassy solid electrolytes are generally soft and thus have a high filling rate. Among them, Li3PS4 glass is known to have a high filling rate. Solid electrolytes containing Li3PS4 glass are disclosed in, for example, Patent Documents 1 to 3.

[0004] However, the ionic conductivity of Li3PS4 glass is low, less than 1 mS / cm.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 5349427

[0008] Patent Document 2: Japanese Patent No. 5521899

[0009] Patent Document 3: Japanese Patent No. 5757284 Summary of the invention

[0010] An object of the present invention is to provide a glass solid electrolyte having a higher filling rate than or equal to that of a conventional glass solid electrolyte and having high ion conductivity.

[0011] According to the present invention, the following glass solid electrolyte and the like are provided.

[0012] 1. A glass solid electrolyte comprising lithium, phosphorus, sulfur, and halogen as constituent elements, wherein the halogen comprises at least bromine,

[0013] The molar ratio (Li / P) of the lithium (Li) to the phosphorus (P) is 2.0 to 5.3,

[0014] The molar ratio (S / P) of the sulfur (S) to the phosphorus (P) is 2.0 to 4.5,

[0015] The molar ratio (X / P) of the halogen (X) to the phosphorus (P) is 0.7 to 2.3, and a peak derived from lithium bromide is shown in powder X-ray diffraction using CuKα rays.

[0016] 2. The glass solid electrolyte according to 1, wherein the crystallite size calculated from the peak half width of the peak with the highest intensity among the peaks derived from lithium bromide is 3 to 60 nm.

[0017] 3. The glass solid electrolyte as described in 1 or 2, wherein the halogen comprises iodine,

[0018] Powder X-ray diffraction using CuKα rays showed a peak derived from lithium iodide.

[0019] 4. The glass solid electrolyte according to 3, wherein the crystallite size calculated from the peak half width of the peak with the highest intensity among the peaks derived from lithium iodide is 3 to 60 nm.

[0020] 5. The glass solid electrolyte according to any one of 1 to 4, wherein the relative density of the powder compact at 400 MPa is 90% or more.

[0021] 6. A glass solid electrolyte as described in any one of 1 to 5, wherein the true density is 2.0 to 3.0 g / cm 3 .

[0022] 7. The glass solid electrolyte according to any one of 1 to 6, wherein the molar ratio (X / P) is greater than 0.75.

[0023] 8. The glass solid electrolyte according to any one of 1 to 6, wherein the molar ratio (X / P) is greater than 0.86.

[0024] 9. The glass solid electrolyte according to any one of 1 to 8, wherein the halogen comprises iodine.

[0025] The molar ratio (I / P) of the iodine (I) to the phosphorus (P) is 2.0 or less,

[0026] The molar ratio (Br / P) of the bromine (Br) to the phosphorus (P) is 0.01 to 1.5.

[0027] 10. The glass solid electrolyte according to any one of 1 to 9, wherein the ion conductivity is 1 mS / cm or more.

[0028] 11. A lithium ion battery comprising the glass solid electrolyte as described in any one of 1 to 10.

[0029] 12. A method for producing a glass solid electrolyte, comprising combining two or more compounds or monomers containing lithium, phosphorus, sulfur, and halogen as constituent elements, wherein the halogen contains at least bromine,

[0030] The molar ratio (Li / P) of the lithium (Li) to the phosphorus (P) is set to 2.0 to 5.3, the molar ratio (S / P) of the sulfur (S) to the phosphorus (P) is set to 2.0 to 4.5, and the molar ratio (X / P) of the halogen (X) to the phosphorus (P) is set to 0.7 to 2.3, and the mixture prepared in this way is vitrified.

[0031] According to the present invention, it is possible to provide a glass solid electrolyte having a higher filling rate than or equal to that of a conventional glass solid electrolyte and having high ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a schematic diagram for explaining a particle density measuring device.

[0033] Figure 2 These are X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 1 to 4.

[0034] Figure 3 These are X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 5 to 8.

[0035] Figure 4 These are X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 9 to 13.

[0036] Figure 5 This is the X-ray diffraction pattern of the glass solid electrolyte prepared in Examples 14 and 15.

[0037] Figure 6 These are X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 16 to 18.

[0038] Figure 7 This is the X-ray diffraction pattern of the glass solid electrolyte prepared in Example 19.

[0039] Figure 8 These are X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 1 to 8.

[0040] Fig. 9 These are X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 9 and 10. DETAILED DESCRIPTION

[0041] In the following, the embodiments of the present invention are described. In addition, in this specification, the upper and lower limits of the numerical ranges of "above", "below", and "to" are numerical values ​​that can be combined arbitrarily, and the numerical values ​​of the embodiments can also be used as the upper and lower limits.

[0042] A glass solid electrolyte according to one embodiment of the present invention includes lithium (Li), phosphorus (P), sulfur (S), and halogen (X) as constituent elements, wherein the halogen (X) includes at least bromine. Furthermore, a molar ratio of the above constituent elements to phosphorus ((Li, S, X) / P) satisfies the following range.

[0043] L i / P=2.0~5.3

[0044] S / P=2.0~4.5

[0045] X / P=0.7~2.3

[0046] In addition, powder X-ray diffraction using CuKα rays showed a peak derived from lithium bromide.

[0047] The glass solid electrolyte of this embodiment has a higher halogen content than the conventional glass solid electrolyte. Thus, a glass solid electrolyte can be obtained, which has a filling rate equal to or higher than that of the conventional glass solid electrolyte and has high ion conductivity. For example, a glass solid electrolyte can be obtained, which has a relative density of 90% or more of a 400 MPa powder compact as an indicator of the filling rate.

[0048] In addition, in the present application, a glass solid electrolyte refers to a solid electrolyte containing a glass (amorphous) component. The presence of a broad peak (halo pattern) caused by an amorphous component in an X-ray diffraction (XRD) measurement can confirm that a glass component is contained. In the XRD measurement of a glass solid electrolyte, a portion of peaks derived from a crystalline component or a peak derived from a raw material can also be observed.

[0049] In one embodiment, the molar ratio (Li / P) of lithium (Li) to phosphorus (P) is preferably 3.0 to 5.25, more preferably 3.5 to 5.20, 3.8 to 5.0, and may further be 4.0 to 4.8.

[0050] The molar ratio of sulfur (S) to phosphorus (P) (S / P) is preferably 3.0 to 4.4, more preferably 3.5 to 4.3, 3.8 to 4.2, and may be further 3.9 to 4.1. By adjusting the molar ratio of sulfur to phosphorus to the above range, there is an effect of reducing the amount of hydrogen sulfide generated in a low dew point environment.

[0051] The molar ratio (X / P) of the halogen (X) to phosphorus (P) is preferably 0.75 to 2.5, more preferably 0.80 to 2.3, 0.85 to 2.0, or 0.90 to 1.8, and may further be 0.95 to 1.5.

[0052] The glass solid electrolyte of this embodiment contains bromine and halogens other than bromine such as fluorine, chlorine, and iodine as constituent elements. The molar ratio (Br / X) of bromine (Br) to halogen (X) is preferably 0.05 to 1.0, more preferably 0.1 to 0.8.

[0053] The molar ratio (Br / P) of bromine (Br) to phosphorus (P) is preferably 0.05 to 2.0, more preferably 0.1 to 1.5, 0.2 to 1.4, or 0.3 to 1.3, and may further be 0.5 to 1.0.

[0054] In one embodiment, the halogen (X) includes bromine and iodine. In addition, the molar ratio (I / P) of iodine (I) to phosphorus (P) is preferably 2.0 or less, more preferably 0.1 to 1.5, 0.2 to 1.4, 0.3 to 1.3, and may further be 0.5 to 1.0.

[0055] The types and molar ratios of the constituent elements of the glass solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.

[0056] The molar ratio of the constituent elements of the glass solid electrolyte can be adjusted by controlling the raw material blending. In addition, the molar ratio of the constituent elements in the raw materials is substantially equal to the molar ratio of the constituent elements of the obtained glass solid electrolyte.

[0057] In the glass solid electrolyte of the present embodiment, the molar ratio (L i / P) and the molar ratio (X / P) preferably satisfy the following formula (1).

[0058] Li / P=(3±α)+X / P (1)

[0059] (wherein α is 0 to 0.5).

[0060] By satisfying formula (1), PS4 as the main skeleton of the glass solid electrolyte 3- The amount of tetrahedral structure generated increases, which has the effect of reducing the amount of hydrogen sulfide generated in a low dew point environment. 3- The larger and more rigid P2S6 4- Structure or P2S7 4- Since the amount of structure generated is reduced, the softness of the glass solid electrolyte can be improved.

[0061] The value α in the formula (1) may be 0 to 0.3, 0 to 0.1, or even 0.

[0062] In one embodiment, the true density of the glass solid electrolyte is preferably 2.0 to 3.0 g / cm 3The true density being within the above range means that the Li3PS4 glass contains a certain amount of halogen, and the halogen contained therein imparts softness to the solid electrolyte and improves the ion conductivity compared to the Li3PS4 glass.

[0063] The true density of the glass solid electrolyte is more preferably 2.05 to 2.9 g / cm 3 , particularly preferably 2.1 to 2.8 g / cm 3 .

[0064] The true density of the glass solid electrolyte can be measured, for example, by a gas phase replacement method using helium (He) gas. Details of the method for measuring the true density of the glass solid electrolyte are described in the Examples.

[0065] In one embodiment, the glass solid electrolyte has a diffraction peak of a lithium halide such as lithium iodide in addition to lithium bromide in a powder X-ray diffraction measurement using CuKα rays. The crystallinity of the lithium halide observed in the powder X-ray diffraction measurement of the glass solid electrolyte is lower than that of the lithium halide as a raw material. By having a diffraction peak of a lithium halide, it is possible to further add softness to the mechanical softness of the glass solid electrolyte itself.

[0066] Among the peaks derived from lithium halide, the position of the peak with the highest intensity is observed, for example, in the range of 2θ of 25 to 30° (deg).

[0067] In one embodiment, the lithium halide is lithium iodide.

[0068] In one embodiment, the crystallite size calculated from the peak half width of the peak with the highest intensity among the peaks derived from lithium bromide is 3 to 60 nm, preferably 5 to 50 nm, and more preferably 7 to 40 nm.

[0069] Generally, the diffraction peak measured by powder X-ray diffraction has a width, and the width of the peak at half the height of the peak after removing the background is called the half width. It is known that the half width is correlated with the crystallite size. The larger the crystallite size, the higher the crystallinity and the higher the repetitive regularity of the crystal structure, so the half width of the diffraction peak measured by powder X-ray diffraction becomes narrower.

[0070] The crystallite size can be adjusted by composition. For example, the crystallite size can be adjusted by adjusting the molar ratio of lithium (Li) to phosphorus (P) (Li / P), the molar ratio of bromine (Br) to halogen (X) (Br / X), and the molar ratio of iodine (I) to phosphorus (P) (I / P).

[0071] When the solid electrolyte is in a glass state, the half width becomes extremely large and the diffraction peak becomes broad.

[0072] In one embodiment, when there is a peak derived from lithium iodide, the crystallite size calculated from the peak half width of the peak with the highest intensity among the peaks is 3 to 60 nm, preferably 5 to 50 nm, and more preferably 7 to 40 nm.

[0073] The peak half width and the crystallite size are calculated by XRD. The details of the measurement and calculation methods are shown in the Examples. In addition, whether there are crystallites, that is, whether peaks of LiBr and LiI are shown, are also obtained by the above calculation method.

[0074] The calculation target of the peak half width is, for example, a diffraction peak at 2θ=28±1° in the case of LiBr, and a diffraction peak at 2θ=25.5±1° in the case of LiI.

[0075] The glass solid electrolyte of the present embodiment has a higher filling rate than or equal to that of conventional glass solid electrolytes and has high ion conductivity.

[0076] Specifically, the relative density of the 400 MPa powder compact, which is an indicator of the filling rate, can be set to 90% or more. The relative density can also be set to 90.5% or more, or 91% or more. In addition, the upper limit of the relative density is not particularly limited, but is usually 99% or less.

[0077] In the present invention, the relative density of the 400 MPa powder compact refers to the ratio of the density of the glass solid electrolyte powder when compressed at 400 MPa (referred to as particle density) to the true density of the glass solid electrolyte (relative density (%) = particle density × 100 / true density). The higher the relative density, the higher the filling rate.

[0078] The details of the method for measuring the relative density of a 400 MPa powder compact are described in the Examples.

[0079] Furthermore, the ion conductivity of the glass solid electrolyte of the present embodiment can be 1 mS / cm or more, and can also be 1.1 mS / cm or more.

[0080] The glass solid electrolyte of the present embodiment can be produced by, for example, mixing starting materials of a known lithium ion sulfide solid electrolyte so that the molar ratio of the constituent elements satisfies a predetermined range, and then vitrifying the mixture.

[0081] As the starting material, two or more compounds or monomers containing lithium, phosphorus, sulfur, and halogen as constituent elements can be used in combination, and any material can be used without particular limitation as long as it exhibits ion conductivity due to the metal atoms contained therein.

[0082] Examples of raw materials containing lithium (Li) include lithium compounds such as lithium sulfide (Li2S), lithium oxide (Li2O), and lithium carbonate (Li2CO3), and lithium metal monomers, etc. Among them, lithium compounds are preferred, and lithium sulfide is more preferred.

[0083] Although the above-mentioned lithium sulfide can be used without particular limitation, high-purity lithium sulfide is preferred. For example, lithium sulfide can be produced by the methods described in Japanese Patent Application Laid-Open Nos. 7-330312, 9-283156, 2010-163356, and 2011-84438.

[0084] Specifically, lithium hydroxide and hydrogen sulfide are reacted at 70° C. to 300° C. in a hydrocarbon organic solvent to generate lithium hydrosulfide, and then the reaction solution is desulfurized to synthesize lithium sulfide (Japanese Patent Application Laid-Open No. 2010-163356).

[0085] Alternatively, lithium sulfide can be synthesized by reacting lithium hydroxide and hydrogen sulfide at 10° C. to 100° C. in an aqueous solvent to generate lithium hydrosulfide, and then desulfurizing and hydrogenating the reaction solution (Japanese Patent Application Laid-Open No. 2011-84438).

[0086] As raw materials containing phosphorus (P), for example, phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5), phosphorus compounds such as sodium phosphate (Na3PO4), and phosphorus monomers can be cited. Among them, phosphorus sulfide is preferred, and phosphorus pentasulfide (P2S5) is more preferred. Phosphorus compounds such as phosphorus pentasulfide (P2S5) and phosphorus monomers can be used without particular limitation as long as they are industrially manufactured and sold.

[0087] As the raw material containing halogen (X) as a constituent element, for example, a halogen compound represented by the following formula is preferably contained.

[0088] M l -X m

[0089] In the formula, M represents sodium (Na), lithium (Li), boron (B), aluminum (Al), silicon (Si), phosphorus (P), sulfur (S), germanium (Ge), arsenic (As), selenium (Se), tin (Sn), antimony (Sb), tellurium (Te), lead (Pb), bismuth (Bi), or a substance obtained by bonding oxygen or sulfur to these elements, preferably lithium (Li) or phosphorus (P), more preferably lithium (Li).

[0090] X is a halogen element selected from fluorine (F), chlorine (Cl), bromine (Br) and iodine (I).

[0091] In addition, l is an integer of 1 or 2, and m is an integer of 1 to 10. When m is an integer of 2 to 10, that is, when there are a plurality of Xs, Xs may be the same or different. For example, in SiBrCl3 described later, m is 4, and X is composed of different elements such as Br and Cl.

[0092] Specific examples of the halogen compound include sodium halides such as NaI, NaF, NaCl, and NaBr; lithium halides such as LiF, LiCl, LiBr, and LiI; boron halides such as BCl3, BBr3, and BI3; aluminum halides such as AlF3, AlBr3, AlI3, and AlCl3; silicon halides such as SiF4, SiCl4, SiCl3, Si2Cl6, SiBr4, SiBrCl3, SiBr2Cl2, and SiI4; phosphorus halides such as PF3, PF5, PCl3, PCl5, POCl3, PBr3, POBr3, PI3, P2Cl4, and P2I4; 10 , SCl2, S2Cl2, S2Br2 and other sulfur halides; GeF4, GeCl4, GeBr4, Ge I4, GeF2, GeCl2, GeBr2, Ge I2 and other germanium halides; AsF3, AsCl3, AsBr3, As I3, AsF5 and other arsenic halides; SeF4, SeF6, SeCl2, SeCl4, Se2Br2, SeBr4 and other selenium halides; SnF4, SnCl4, SnBr4, Sn I4, SnF2, SnCl2, SnBr2, Sn I2 and other tin halides; SbF3, SbCl3, SbBr3, Sb I3, SbF5, SbCl5 and other antimony halides; TeF4, Te2F 10 , TeF6, TeC l2, TeC l4, TeBr2, TeBr4, Te I4 and other tellurium halides; PbF4, PbC l4, PbF2, PbC l2, PbBr2, Pb I2 and other lead halides; BiF3, BiC l3, BiBr3, BiI3 and other bismuth halides, etc.

[0093] Among them, lithium halides such as lithium chloride (LiCl), lithium bromide (LiBr), and lithium iodide (LiI), and phosphorus halides such as phosphorus pentachloride (PCl5), phosphorus trichloride (PCl3), phosphorus pentabromide (PBr5), and phosphorus tribromide (PBr3) are preferably exemplified. Among them, lithium halides such as LiCl, LiBr, and LiI, and PBr3 are preferred, lithium halides such as LiCl, LiBr, and LiI are more preferred, and LiI and LiBr are more preferred.

[0094] As the halogen compound, one of the above compounds may be used alone, or two or more thereof may be used in combination. That is, at least one of the above compounds may be used.

[0095] In this embodiment, the raw material preferably comprises a lithium compound, a phosphorus compound, and a halogen compound, the halogen compound contains at least bromine, and at least one of the lithium compound and the phosphorus compound contains sulfur. It is more preferably a combination of lithium sulfide, phosphorus sulfide and two or more lithium halides, and further preferably a combination of lithium sulfide, phosphorus pentasulfide and two or more lithium halides.

[0096] For example, when lithium sulfide, phosphorus pentasulfide, or two or more lithium halides are used as raw materials for a glass solid electrolyte, the molar ratio of lithium sulfide to phosphorus pentasulfide in the raw materials is preferably 65 to 85:15 to 35, more preferably 70 to 80:20 to 30, further preferably 72 to 78:22 to 28, and particularly preferably 75:25.

[0097] In addition, when the amount of Li3PS4 calculated based on the constituent elements Li, P and S of lithium sulfide and phosphorus pentasulfide is set to 100 mol parts, it is preferred to set the lithium halide to 75 to 250 mol parts, more preferably 80 to 225 mol parts, and it can also be set to 85 to 200 mol parts, 90 to 175 mol parts, or 95 to 150 mol parts.

[0098] In this embodiment, mechanical stress is applied to the above raw materials to make them react, thereby making a glass solid electrolyte. Here, "applying mechanical stress" refers to mechanically applying shear force or impact force, etc. As a way of applying mechanical stress, for example, a pulverizer or kneader such as a star ball mill, a vibration mill, and a rolling mill can be used. The pulverization and mixing are carried out by strong mechanical stress until at least a part of the raw material powder becomes a state in which the crystallinity cannot be maintained.

[0099] As the condition of pulverizing and mixing, for example, when a planetary ball mill is used as a pulverizer, the rotation speed is set to tens to hundreds of revolutions per minute, and the treatment is performed for 0.5 hours to 100 hours. More specifically, in the case of the planetary ball mill (model P-5 manufactured by FRITSCH) used in the embodiments of the present application, the rotation speed of the planetary ball mill is preferably 100 rpm to 400 rpm, and more preferably 150 rpm to 300 rpm. The temperature during pulverization can be set to room temperature. In this case, no external cooling is performed. For example, a 5-minute stop period can be set every hour. In addition, if it is under the condition that there is no crystallization during pulverization, it is also possible not to set a stop period, and pulverize while cooling.

[0100] When using zirconia balls as the grinding medium, for example, the diameter thereof is preferably 0.2 to 20 mm.

[0101] The filling rate of the glass solid electrolyte of this embodiment is equal to or higher than that of the conventional glass solid electrolyte, and it has high ion conductivity, so it can be preferably used in batteries. It is particularly preferred when lithium is used as the conductive material. The glass solid electrolyte of this embodiment can be used in the positive electrode layer, the negative electrode layer, and the electrolyte layer.

[0102] A lithium ion battery according to one embodiment of the present invention includes the glass solid electrolyte of the present invention described above. For example, an all-solid lithium ion battery can be manufactured by using the glass solid electrolyte of the present invention instead of a liquid electrolyte.

[0103] All-solid lithium-ion batteries are mainly composed of a positive electrode layer, a negative electrode layer and an electrolyte layer, and the glass solid electrolyte of the present invention can be used in any layer. In addition, each layer can be manufactured by a known method.

[0104] For example, when used for a positive electrode layer or a negative electrode layer, a positive electrode active material or a negative electrode active material is mixed and dispersed in the glass solid electrolyte of the present invention to obtain a positive electrode composite material or a negative electrode composite material.

[0105] As the positive electrode active material, any positive electrode active material can be used without particular limitation as long as it can promote the battery chemical reaction caused by the lithium element, which is preferably used as an element showing ionic conductivity in this embodiment, due to its relationship with the negative electrode active material. As the positive electrode active material that can perform such insertion and extraction of lithium ions, oxide-based positive electrode active materials, sulfide-based positive electrode active materials, etc. can be cited.

[0106] As oxide-based positive electrode active materials, preferred examples include lithium-containing transition metal composite oxides such as LMO (lithium manganese oxide), LCO (lithium cobalt oxide), NMC (lithium nickel cobalt manganese oxide), NCA (lithium nickel cobalt aluminum oxide), LNCO (lithium nickel cobalt oxide), and olivine-type compounds (LiMeNPO4, Me=Fe, Co, Ni, Mn).

[0107] Examples of the sulfide-based positive electrode active material include titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), and nickel sulfide (Ni3S2).

[0108] In addition to the above-mentioned positive electrode active materials, niobium selenide (NbSe 3 ) or the like can also be used.

[0109] In this embodiment, one type of positive electrode active material can be used alone or in combination of two or more types.

[0110] As the negative electrode active material, any negative electrode active material can be used without particular limitation as long as it can promote the battery chemical reaction accompanying the movement of lithium ions, wherein the battery chemical reaction is caused by the element preferably used as the element showing ion conductivity in this embodiment, preferably a metal that can form an alloy with the lithium element, its oxide, an alloy of the metal and the lithium element, etc., preferably lithium element. As the negative electrode active material that can perform such insertion and extraction of lithium ions, any material known as a negative electrode active material in the battery field can be used without limitation.

[0111] Examples of such negative electrode active materials include metallic lithium such as metallic lithium, metallic indium, metallic aluminum, metallic silicon, and metallic tin, or metals capable of forming alloys with metallic lithium, oxides of these metals, or alloys of these metals with metallic lithium.

[0112] The electrode active material used in the present embodiment may have a coating layer on the surface of which is coated.

[0113] As a material for forming the coating layer, an element showing ionic conductivity in the crystalline sulfide solid electrolyte used in this embodiment can be cited, preferably an ion conductor such as a nitride, an oxide, or a composite of lithium. Specifically, lithium nitride (Li3N), a Li4GeO4-based structure such as Li 4-2x Zn x Conductors with a crystalline lithium superion conductor (LI SI CON) type crystal structure such as GeO4, conductors with a Li3PO4 type skeleton structure such as Li 4-x Ge 1-x P xS4 and other conductors with sulfide crystal lithium superion conductor (thio-LISI CON) type crystal structure, La 2 / 3-x Li 3x Conductors with a perovskite crystal structure such as TiO3, conductors with a sodium superion conductor (NASI CON) crystal structure such as LiTi2(PO4)3, etc.

[0114] In addition, Li y T i 3-y O4(0<y<3)、Li4Ti5O 12 Conductors such as lithium titanate (LTO), lithium metal oxides of metals belonging to Group 5 of the periodic table such as LiNbO3, LiTaO3, or oxide-based conductors such as Li2O-B2O3-P2O5, Li2O-B2O3-ZnO, and Li2O-Al2O3-SiO2-P2O5-TiO2.

[0115] The electrode active material having a coating layer can be obtained, for example, by attaching a solution containing various elements constituting a material for forming the coating layer to the surface of the electrode active material and calcining the attached electrode active material preferably at 200° C. to 400° C.

[0116] Here, as the solution containing various elements, for example, a solution containing alkoxides of various metals such as lithium ethoxide, titanium isopropoxide, niobium isopropoxide, tantalum isopropoxide, etc. can be used. In this case, as the solvent, an alcohol solvent such as ethanol and butanol; an aliphatic hydrocarbon solvent such as hexane, heptane, octane; an aromatic hydrocarbon solvent such as benzene, toluene, xylene, etc. can be used.

[0117] In addition, the above-mentioned attachment may be performed by dipping, spraying, or the like.

[0118] From the viewpoint of improving manufacturing efficiency and battery performance, the firing temperature is preferably 200° C. to 400° C., more preferably 250° C. to 390° C., and the firing time is usually about 1 minute to 10 hours, preferably 10 minutes to 4 hours.

[0119] As the coating rate of coating layer, it is preferably more than 90% based on the surface area of ​​electrode active material, more preferably more than 95%, and further preferably 100%, that is, preferably the whole face is coated. In addition, the thickness of coating layer is preferably more than 1nm, more preferably more than 2nm, and is preferably below 30nm as the upper limit, more preferably below 25nm.

[0120] The thickness of the coating layer can be measured by cross-sectional observation using a transmission electron microscope (TEM), and the coverage ratio can be calculated from the thickness of the coating layer, elemental analysis values, and BET specific surface area.

[0121] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer and the negative electrode layer, and the current collector can use a known current collector. For example, a layer obtained by coating a substance that reacts with the above-mentioned glass solid electrolyte with Au, Pt, Al, Ti or Cu, etc. can be used.

[0122] Example

[0123] Hereinafter, the present invention will be described in detail based on examples. The embodiments of the present invention are not limited to the examples. The evaluation method of the glass solid electrolyte prepared in each example is as follows.

[0124] (1) Powder X-ray diffraction (XRD) measurement

[0125] The powder of the glass solid electrolyte prepared in each example was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm and leveled with glass. The filled sample was measured with a kapton film without contact with air using XRD. The 2θ position of the diffraction peak was determined by Le Bail analysis using the XRD analysis program RI ETAN-FP.

[0126] Powder X-ray diffraction measurement was carried out under the following conditions.

[0127] Device used: BRUKER D2 PHASER

[0128] Tube voltage: 30kV

[0129] Tube current: 10mA

[0130] X-ray wavelength: Cu-Kα ray

[0131] Optical system: Concentration method

[0132] Slit configuration: Sola slit 4°, divergence slit 1mm, Kβ filter (N i plate)

[0133] Detector: Semiconductor detector

[0134] Measuring range: 2θ=10-60°(deg)

[0135] Step width, scanning speed: 0.05°, 0.05° / sec

[0136] In the analysis of the peak position for confirming the presence of the crystal structure from the measurement results, the peak position was determined by correcting the baseline using an 11th-order Legendre orthogonal polynomial using an XRD analysis program, RIETA N-FP.

[0137] (2) Peak half width

[0138] The peak half width was calculated from the peak at 2θ=25.5±1° in the case of LiI, and was calculated from the peak at 2θ=28±1° in the case of LiBr.

[0139] The half width parameter E is determined so that the difference between the measured value of the intensity (vertical axis value of the XRD pattern) and the calculated value described below is minimized within the range where the peak exists (2θ=24.5 to 26.5° or 2θ=27 to 29°).

[0140] The ratio of the Lorentz function is set to A (0≤A≤1), the intensity correction value is set to B, the angle of 2θ at which the intensity is maximum is set to C, the angle (2θ) of the calculated intensity is set to D, the half-width parameter is set to E, the background is set to F, the measured value of the intensity at the angle (2θ) of the calculated intensity is set to G, and the variables are set to A, B, C, E and F. For each angle (2θ) at which the intensity is measured, the deviation H between the measured value and the calculated value of the intensity is calculated by the following formula (3).

[0141] H=G-{B×{A / (1+(DC) 2 / E 2 )+(1-A)×exp(-1×(DC) 2 / E 2 )}+F} (3)

[0143] The variables were determined by summing H within the range of 2θ=24.5-26.5° or 2θ=27-29° and minimizing the sum of H in a GRG nonlinear manner using the solver function of spreadsheet software (Excel, Microsoft).

[0144] The half width is calculated by the following formula (4) using the obtained half width parameter E.

[0145] Half width = E × 2 × (l n4) (1 / 2) (4)

[0146] When the peak intensity is calculated to be zero, the half-width parameter cannot be calculated either, and thus no peak exists at this time, that is, no peak derived from LiI or LiBr is shown, and it can be considered that no crystallite exists.

[0147] (3) Crystallite size

[0148] The half width calculated by the above method is set as b. In addition, in order to correct the expansion of the half width from the device, the half width is corrected using the NI ST standard Si (640d, crystallite size 525nm). If the half width from the device after correction is set as B correct , then the corrected half width β of the crystallite size is calculated as shown in the following formula (5).

[0149] β=b―B correct (5)

[0150] The actual crystallite size L can be calculated by the following formula (6).

[0151] L = K × λ / (β cos (C / 2)) (6)

[0152] Here, the constant K is set to 0.9, and the wavelength of the X-ray used in the measurement is used as λ. In addition, C is 2θ of the center of the maximum peak position when calculating the peak half width as described above.

[0153] (4) Relative density of 400MPa powder compact

[0154] (Measurement of true density)

[0155] True density is measured by using the gas phase replacement method (M i crotracBEL company: BELMAX) of helium (He) gas. Calculate the volume inside the sample cell when the pressure of helium (He) gas is set to 55KPa, 60KPa, 65KPa, 70KPa, 75KPa, 80KPa, 85KPa, 90KPa, 95KPa, 100KPa, 105Kpa and 110KPa, and set the average value as the internal volume of the sample cell. In addition, the sample cell weight is calculated using an electronic balance. The capacity and weight of the empty (bl ank) sample cell are measured 3 times by the above method, and the average value is set as the empty sample cell capacity V1, and the weight is set as the empty sample cell weight W1. The glass solid electrolyte is put into the sample cell, and the capacity of the gas phase part of the sample cell at this time and the total weight of the sample cell are measured 3 times by the above method, and the average value is set as the capacity V2 excluding the sample, and the total weight of the sample cell is set as W2.

[0156] True density of glass solid electrolyte d (g / cm 3 ) is calculated by the following formula (7).

[0157] d=(W2―W1) / (V1―V2) (7)

[0158] In addition, the true density of the sample is set to the average value of the true density d calculated three times according to the above operation and the above formula. The standard deviation of the true density calculated by this method is 0.05 g / cm 3the following.

[0159] (Measurement of particle density)

[0160] A schematic diagram of the particle density measurement device is shown in Figure 1 shown.

[0161] The sample 10 was filled into a cylindrical jig 11 (manufactured by MACOR (registered trademark)) and pressurized at 400 MPa using a uniaxial press via a stainless steel piston 12. The length L of the device in a state (bl ank) without the sample filled was int , and the length L of the device containing the pressurized sample after The height of the sample (particle) is measured by the difference in pellet .

[0162] Specifically, the piston 12 is inserted to a diameter of 10 mm (cross-sectional area S pellet : 0.785cm 2 ) of the cylindrical fixture 11. The cylindrical fixture 11 is rotated 90° in a direction perpendicular to the pressurizing direction, and four measurements are performed, and the average value is set as L int (cm). At this time, the bolt 13 and the nut 14 were tightened at 8 N·m using a torque wrench, and the measurement was performed while the piston 12 was pressurized.

[0163] Next, 0.3 g of the powder of the glass solid electrolyte as a sample is weighed by an electronic balance and put into the cylindrical fixture 11. After being put in, the piston 12 is pressurized by a uniaxial press, thereby pressurizing the sample. The pressure is set to 185 MPa and maintained for 2 minutes, and then the pressure is released. The sample cell is rotated 120° in a direction perpendicular to the pressurization direction, and pressurized in the same manner. Then, it is rotated 120° again and pressurized in the same manner. Next, the pressure is set to 400 MPa, and the sample is pressurized in the same manner as in the case of 185 MPa.

[0164] After forming, with L int Repeat the measurement 4 times and set the average value as L. after (cm). Particle density d pel let It is calculated by the following formula (8).

[0165] d pellet =0.3 / {(L after -L int )×S pellet} (8)

[0166] (Calculation of relative density)

[0167] It is calculated by the following formula (9).

[0168] Relative density (%) = particle density × 100 / true density (9)

[0169] (5) Ionic conductivity

[0170] The glass solid electrolyte prepared in each example was formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2 ), round particles with a height (L) of 0.1 to 0.3 cm, thus making a sample. The top and bottom of the sample were taken as electrode terminals, and measured by the AC impedance method at 25°C (frequency range: 5 MHz to 0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is set as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.

[0171] R=ρ(L / S)

[0172] σ=1 / ρ

[0173] (6) I CP measurement

[0174] The powder of the solid electrolyte produced in each example was weighed and collected in a vial under an argon atmosphere. A KOH alkaline aqueous solution was added to the vial, and the sample was dissolved while being careful to capture the sulfur component, and appropriately diluted to prepare a measurement solution. It was measured by a Paschen-Runge type I CP-OES device (SPECTROARCOS manufactured by SPECTRO) to determine its composition.

[0175] The standard curve solutions of Li, P, and S were prepared using 1000 mg / L standard solutions for ICP measurement, and the standard curve solutions of Cl and Br were prepared using 1000 mg / L standard solutions for ion chromatography.

[0176] Two measurement solutions were prepared for each sample, and each measurement solution was measured five times to calculate the average value. The composition was determined from the average value of the measurement values ​​of the two measurement solutions.

[0177] Example 1

[0178] [Production of glass solid electrolyte]

[0179] (1) Preparation of glass solid electrolyte

[0180] Lithium sulfide was weighed to give 2.366 g, phosphorus pentasulfide to give 3.815 g, lithium iodide to give 3.446 g, and lithium bromide to give 0.373 g, and 600 g of 10 mm diameter zirconia balls were placed in a 500 mL zirconia can and sealed. Table 1 shows the molar ratio of the starting materials.

[0181] The resulting mixture was pulverized (mechanically ground) using a planetary ball mill (FRITSCH, Model P-5) at room temperature and at a rotation speed of 220 rpm for 40 hours to obtain a glass solid electrolyte.

[0182] Table 1 shows the raw material composition ratio, the molar ratio of each element to phosphorus (P), and the evaluation results.

[0183] Examples 2 to 19, Comparative Examples 1 to 10

[0184] A glass solid electrolyte was prepared in the same manner as in Example 1 except that the raw material composition ratio was changed as shown in Table 1. Table 1 shows the evaluation results.

[0185] In Table 1, the amount of Li3PS4 is set to 100 mol parts, which is equivalent to 150 mol parts of Li2S4 and 50 mol parts of P2S5 as the starting materials.

[0186] The molar ratio (X / P) of each element of the glass solid electrolyte to phosphorus (P) was measured by ICP for Examples 7, 14, 16 and Comparative Examples 1 and 7. The results are shown below.

[0187] Example 7: Li / P = 4.4, S / P = 3.9, Br / P = 0.25, I / P = 1.26

[0188] Example 14: Li / P = 3.9, S / P = 3.9, Br / P = 0.53, I / P = 0.52

[0189] Example 16: Li / P = 4.0, S / P = 4.0, Br / P = 1.05

[0190] Comparative Example 1: Li / P = 3.0, S / P = 4.0

[0191] Comparative Example 7: Li / P = 4.4, S / P = 4.0, I / P = 1.52

[0192] [Table 1]

[0193]

[0194] Figure 2 X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 1 to 4 are shown. Figure 3 X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 5 to 8 are shown. Figure 4 X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 9 to 13 are shown. Figure 5 X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 14 and 15 are shown. Figure 6 X-ray diffraction patterns of the glass solid electrolytes prepared in Examples 16 to 18 are shown. Figure 7 The X-ray diffraction pattern of the glass solid electrolyte prepared in Example 19 is shown. Figure 8 X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 1 to 8 are shown. Fig. 9 X-ray diffraction patterns of the glass solid electrolytes prepared in Comparative Examples 9 and 10 are shown.

[0195] From the XRD measurement results, it was confirmed that the glass solid electrolytes produced in Examples 1 to 19 were amorphous and that a portion of the lithium halide as a raw material was present in a crystallized state.

[0196] Industrial Applicability

[0197] The glass solid electrolyte of the present invention is preferably used as a constituent material of a lithium ion battery. In addition, the lithium ion battery of the present invention can be preferably used, for example, in batteries used in information-related equipment such as personal computers, cameras and mobile phones, or communication equipment, and vehicles such as electric cars.

[0198] Several embodiments and / or examples of the present invention have been described in detail above, but it is easy for those skilled in the art to add more changes to these illustrative embodiments and / or examples without departing from the novel teachings and effects of the present invention. Therefore, these more changes are also included in the scope of the present invention.

[0199] The contents of all the documents described in this specification and the applications serving as the basis for the priority claim based on the Paris Convention of the present application are hereby cited.

Claims

1. A glass solid electrolyte, characterized in that: Containing lithium, phosphorus, sulfur, and halogen as constituent elements, wherein the halogen includes at least bromine, The molar ratio (Li / P) of the lithium (Li) to the phosphorus (P) is 2.0 to 5.3, The molar ratio (S / P) of the sulfur (S) to the phosphorus (P) is 2.0 to 4.5, The molar ratio (X / P) of the halogen (X) to the phosphorus (P) is 0.7 to 2.3, Powder X-ray diffraction using CuKα rays showed a peak derived from lithium bromide.

2. The glass solid electrolyte according to claim 1, characterized in that The crystallite size calculated from the peak half width of the peak with the highest intensity among the peaks derived from lithium bromide is 3 to 60 nm.

3. The glass solid electrolyte according to claim 1 or 2, characterized in that: The halogen comprises iodine, Powder X-ray diffraction using CuKα rays showed a peak derived from lithium iodide.

4. The glass solid electrolyte according to claim 3, characterized in that The crystallite size calculated from the peak half width of the peak with the highest intensity among the peaks derived from lithium iodide is 3 to 60 nm.

5. The glass solid electrolyte according to any one of claims 1 to 4, characterized in that The relative density of the 400MPa powder compact is above 90%.

6. The glass solid electrolyte according to any one of claims 1 to 5, characterized in that True density is 2.0~3.0g / cm 3 .

7. The glass solid electrolyte according to any one of claims 1 to 6, characterized in that The molar ratio (X / P) is greater than 0.

75.

8. The glass solid electrolyte according to any one of claims 1 to 6, characterized in that The molar ratio (X / P) is greater than 0.

86.

9. The glass solid electrolyte according to any one of claims 1 to 8, characterized in that The halogen comprises iodine, The molar ratio (I / P) of the iodine (I) to the phosphorus (P) is 2.0 or less, The molar ratio (Br / P) of the bromine (Br) to the phosphorus (P) is 0.01 to 1.

5.

10. The glass solid electrolyte according to any one of claims 1 to 9, characterized in that: The ionic conductivity is above 1 mS / cm.

11. A lithium ion battery, characterized in that: Contains the glass solid electrolyte according to any one of claims 1 to 10.

12. A method for manufacturing a glass solid electrolyte, characterized in that: Combining two or more compounds or monomers containing lithium, phosphorus, sulfur, and halogen as constituent elements, wherein the halogen contains at least bromine, The molar ratio (Li / P) of the lithium (Li) to the phosphorus (P) is set to 2.0 to 5.3, the molar ratio (S / P) of the sulfur (S) to the phosphorus (P) is set to 2.0 to 4.5, and the molar ratio (X / P) of the halogen (X) to the phosphorus (P) is set to 0.7 to 2.3, and the mixture prepared in this way is vitrified.

Citation Information

Patent Citations

  • Photo sensitive material

    JP1978049427A

  • Electrically connecting device

    JP1980021899A

  • Nuclear reactor emergency shutdown device

    JP1982057284A

  • Production of lithium sulfide

    JP1995330312A

  • Lithium ion conductive solid electrolyte and its manufacture

    JP1997283156A